2018
DOI: 10.19044/esj.2018.v14n2p244
|View full text |Cite
|
Sign up to set email alerts
|

English Pronunciation Errors Made by Saudi Students

Abstract: Arabs often pronounce many English words wrongly which leads to spelling and writing errors. This paper deals with English pronunciation errors made by two groups of native Saudi Arab speakers. The students in the first group are of English major while the students in the second group are of Arabic major. Generally, Arabic speakers use direct transfer and interference from Arabic in addition to stress shifts in their pronunciation that are not recognized stress patterns in English. Also, there are some sounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 10 publications
(4 reference statements)
1
20
0
1
Order By: Relevance
“…Undoubtedly, pronunciation is an essential skill for mastering any foreign language, as communication depends on accurate pronunciation (Kharma and Hajjaj 1989).Pronunciation is described to be a complex aspect in learning a language. It is also a very delicate matter as mispronounced segments and suprasegments can cause listener disorientation and comprehension inhibition (Ababneh 2018;Hassan 2014). Few researchers have concluded that such errors are caused by linguistic factors, Hassan (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly, pronunciation is an essential skill for mastering any foreign language, as communication depends on accurate pronunciation (Kharma and Hajjaj 1989).Pronunciation is described to be a complex aspect in learning a language. It is also a very delicate matter as mispronounced segments and suprasegments can cause listener disorientation and comprehension inhibition (Ababneh 2018;Hassan 2014). Few researchers have concluded that such errors are caused by linguistic factors, Hassan (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many previous studies have been concerned with teaching and learning pronunciation, identifying the most common pronunciation problems among students of various nationalities such as Korean, Spanish, French and Arab. These studies have tried to categorize pronunciation problems, to discover the reasons that hinder non-native students from pronouncing foreign sounds correctly, and to offer some recommendations on how to fix these problems among EFL students (Ababneh 2018;Altaha, 1995;Binturk, 2008;Hago and Khan 2015;Gilakjaniand Ahmadi 2011;Hassan 2014; Jabaliand Abuzaid2017; Kalaldeh 2016). Altaha (1995) and Kharma and Hajjaj, (1989) concluded that the most problematic English consonant sounds among Arab EFL learners are /ŋ/, /p/, / ɫ/, /ɹ/, /ʒ/,/ tʃ/ in addition to other errors such as replacing /v/ with /f/ and breaking consonant clusters (epenthesis).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only very view studies have been conducted on the accuracy of pronouncing the problematic sounds produced by Arab EFL learners using Praat software such as the study by Ali (2013). In the current body of literature, there are many studies that have already proven the difficulty in pronouncing the English affricate /tʃ/, as well as some other English sounds that are absent in Arabic Language for Arabic learners of English Language such as the studies by Alqarni (2013), Elmahdi and Khan (2015), Al Yaqoobi, Ali and Sulan (2016), Jabali and Abuzaid (2017), and Ababneh (2018). They found that the /tʃ/ is sometimes pronounced as /ʃ/ by Arab learners of English Language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He concluded that learners used reduction, substitution and/or deletion as alternative processes for their incorrect pronunciation of these clusters. In a similar context, (Ababneh, 2018) compared pronunciation errors of two Saudi groups: one was studying English major and the second was studying Arabic major in order to find out the effect of the first language sound system on participants' pronunciation of English sounds. While it was found that there were no significant errors between the two groups, there was a strong correlation between the period of study and the number of pronunciation errors committed while learning EFL i.e., EFL learners who studied language for more spans of time showed less pronunciation problems than those studied this major for shorter period of time.…”
Section: Literature Reviewmentioning
confidence: 99%